Application of Burhani Epistemology to Science Verses (Applied Studies in the Book of Science Verses) - Bayu Al Badjie Hasan; Sawaluddin Siregar; Dalmi Iskandar Sultani; Nida Husna Abdul Malik; Muhammad Faisal; Andri Nirwana AN (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
based on rationality. The relevance of Islam and science in several books written by several authors have different perspectives, for example Achmad Baiquni, namely linking verses from the Koran to science and technology, especially science with the Islamization of science, justification and sacralization patterns. M Amin Abdullah's Islamic relationship to science is the Theo anthropocentric concept of Interconnection Integration with the symbol of a Spider Web. leads to the Islamization of integration typology science. Meanwhile, Agus Purwanto is the relation of Islamic science in the construction of Islamic science with an approach to Kauniyyah verses including the integration variant of the Islamization of science pattern. What about the Book of Tafsir Verses on Science written by Andri Nirwana? This research is qualitative research, critical discourse analysis, the study of scientists' thinking using document studies in the form of books, journals, diktats and other notes. As well as adding direct interviews with the author to confirm any required data. This article finds the results of an analysis study of Islamic science relations carried out on Andri Nirwana's thoughts. Andri Nirwana is the author of a book that applies Reasoning Burhani in the Kauniyyah verses approach, he tries to break down the pattern of Islamic science relations in the book